The Impact of COVID-19 and Structural Market Changes on the Greek Stock Market: An Empirical Analysis - Christodoulou-Volos, Christos; Tserkezos, Dikaios (International Journal of Economics and Financial Issues, 2024)
This study examines the dual impact of COVID-19 and structural market changes on the Greek stock market, specifically the Athens stock exchange (ASE). Quantitative data analysis, granger causality models, and Hsiao’s approach to granger causality were employed to investigate the causalities between COVID-19 pandemic measures and ASE returns. Our findings reveal that pandemic-related variables, including lockdown measures and mobility restrictions, significantly negatively affected the ASE by disrupting economic activities and diminishing investor confidence. Conversely, the study also highlights the positive impact of monetary policy interest rates on the market, which helped stabilize the financial environment by lowering borrowing costs and stimulating investment. These results underscore the intricate dynamics between crisis-induced restrictions and monetary policy adjustments, offering valuable insights for policymakers and investors navigating economic uncertainties.